Nghiên cứu tổng hợp perovskit LaMn0,5Cu0,5O3 có kích thước nanomet bằng phương pháp sol gel xitrat - Đại, Lưu Minh; Dũng, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
LaMn0.5Cu0.5O3 was synthesized as nanoparticles with relatively high surface area (16.6 m2/g) at temperature 650oC from gel precursor prepared by using citric acid (AC) and corresponding metal nitrates. The influence of pH, citric acid/metals mole ratio and temperature of gel formation on the crystallization of perovskites was studied. The Samples were characterized by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), field emission scanning electron microscopy (FE-SEM) and BET (Brunaure-Emmet-Teller) measurements.